The Effect of Cultural Intelligence, Service Training, and Organizational Culture on Employee Loyalty: The Mediating Role of Work-Life Balance at Pusat Oleh-Oleh Shinta Lampung - Siti Patma Ima; Ria Nida Yuniarti; Fera Ardita; Febrianty Febrianty; Reza Rahardian Pratama (IJBLE Scientific Publications Community Inc., 2026)
This study examines the effects of cultural intelligence, service training, and organizational culture on employee loyalty, with work-life balance as an intervening variable among employees of Pusat Oleh-Oleh Shinta Lampung. The study applies a quantitative causal-associative design. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS. The measurement model was assessed through outer loadings, Cronbach's Alpha, composite reliability, Average Variance Extracted (AVE), Heterotrait-Monotrait Ratio (HTMT), and Variance Inflation Factor (VIF), while the structural model was evaluated through R-square, f-square, path coefficients, t-statistics, p-values, and specific indirect effects. The results indicate that cultural intelligence does not have a significant effect on either work-life balance (O = 0.139; t = 0.779; p = 0.436) or employee loyalty (O = -0.051; t = 0.424; p = 0.671). In contrast, service training has a positive and significant effect on work-life balance (O = 0.593; t = 3.931; p = 0.000) and employee loyalty (O = 0.387; t = 3.816; p = 0.000). Work-life balance also has a positive and significant effect on employee loyalty (O = 0.554; t = 5.804; p = 0.000) and mediates the effect of service training on employee loyalty (O = 0.328; t = 2.965; p = 0.003). The source manuscript additionally reports that work-life balance mediates the effect of organizational culture on employee loyalty based on the Sobel test (Z = 2.266; p = 0.023), although the complete PLS-SEM path coefficients for organizational culture were not provided in the available output tables. The findings suggest that, in a tourism-oriented retail SME context, employee loyalty is shaped more strongly by service training and work-life balance than by cultural intelligence as a direct predictor.